Implementasi Manajemen Berbasis Sekolah Sebagai Upaya Peningkatan Kualitas Pembelajaran Di Sekolah Standar Nas - Eka Putra (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Implementation of School-Based Management as an Effort to Improve the Quality of Learning in National Standard SchoolsThis study aims to: (1). Understand the implementation process of School Based Management as an effort to improve the quality of learning in National Standard Schools (2). To find out how the results of implementing School Based Management can improve the quality of learning in National Standard Schools. (3). To find out the obstacles to the implementation of School Based Management in improving the quality of learning in National Standard Schools. This research includes research with a qualitative approach with a population of SD Negeri 001XI Sungai Penuh with samples including: foundations, school committees, principals and teachers and school employees and other school personnel. Data was collected through interviews and observation as well as document analysis to the parties in charge and the results were analyzed descriptively and narratively. The research results show that: (1). That the process of implementing School-Based Management at SD Negeri 001XI Sungai Penuh has been going quite well, this is reflected by the existence of: (a). Support for all staff, (b) SBM phasing, (c) Staff training, (d) budget support, (e) Delegation of authority. (2). In terms of the results of its implementation, the implementation of SBM at SD Negeri 001XI Sungai Penuh as an effort to improve the quality of learning has been running quite efficiently and effectively, this can be seen from: (1) High academic achievement of students, (2) Teachers master material and scientific concepts, (3 ) Appropriate teaching methods, approaches, styles, art, and procedures, (4) Efficient and effective use of facilities, (5) Teacher understanding of group and individual characteristics of students, (6) Creating creative dialogue and a fun learning environment, ( 7) Teacher personality (exemplary) Obstacles in SBM at SD Negeri 001XI SungaiFull are that there are still some teachers/employees who are late in responding to the developing phenomenon, the teaching methods are still conventional, and there is an ewuh pakewuh culture in taking decisions. The suggestion in this study is that foundations and local governments need to provide adequate support for the implementation of SBM. Principals better understand the essence of SBM, teachers need to improve their abilities in order to provide learning services to their students, and Community Participation (PSM) in supporting progress needs to be improved.Abstrak: Implementasi Manajemen Berbasis Sekolah Sebagai Upaya Peningkatan Kualitas Pembelajaran Di Sekolah Standar NasionalPenelitian ini bertujuan untuk; (1). Memahami proses implementasi Manajemen Berbasis Sekolah sebagai upaya peningkatan mutu pembelajaran di Sekolah Standar Nasional (2). Untuk mengetahui bagaimana hasil penerapan Manajemen Berbasis Sekolah dapat meningkatkan mutu pembelajaran di Sekolah Standar Nasional. (3). Untuk mengetahui kendala penerapan Manajemen Berbasis Sekolah dalam meningkatkan mutu pembelajaran di Sekolah Standar Nasional. Penelitian ini termasuk penelitian dengan pendekatan kualitatif dengan populasi SD Negeri 001XI Sungai Penuh dengan sampel antara lain: komite sekolah, kepala sekolah dan guru serta pegawai sekolah dan personel sekolah lainnya. Data dikumpulkan melalui wawancara dan observasi serta analisis dokumen kepada pihak-pihak yang berwenang dan hasilnya dianalisis secara deskriptif dan naratif. Hasil penelitian menunjukkan bahwa: (1). Bahwa proses implementasi MBS di SD Negeri 001XI Sungai Penuh sudah berjalan cukup baik, hal ini tercermin dari adanya: (a). Dukungan untuk semua staf, (b) Pentahapan MBS, (c) Pelatihan staf, (d) dukungan anggaran, (e) Pendelegasian wewenang. (2). Ditinjau dari hasil implementasinya, implementasi MBS di SD Negeri 001XI Sungai Penuh sebagai upaya peningkatan kualitas pembelajaran sudah berjalan cukup efisien dan efektif, hal ini terlihat dari: (1) Prestasi akademik siswa yang tinggi , (2) Guru menguasai materi dan konsep keilmuan, (3) Metode, pendekatan, gaya, seni, dan prosedur mengajar yang tepat, (4) Penggunaan fasilitas yang efisien dan efektif, (5) Guru memahami karakteristik kelompok dan individu siswa, (6) Menciptakan dialog yang kreatif dan suasana belajar yang menyenangkan, (7) Kepribadian guru (teladan) Kendala dalam MBS di SD Negeri 001XI SungaiFull adalah masih adanya guru/pegawai yang terlambat merespon fenomena yang berkembang, metode pengajaran masih konvensional, dan ada budaya ewuh pakewuh dalam mengambil keputusan. Saran dalam penelitian ini adalah pemerintah daerah perlu memberikan dukungan yang memadai untuk pelaksanaan MBS. Kepala sekolah lebih memahami hakikat MBS, guru perlu meningkatkan kemampuannya dalam rangka memberikan layanan pembelajaran kepada siswanya, dan Partisipasi Masyarakat (PSM) dalam mendukung kemajuan perlu ditingkatkan